Digital phenotyping of coconut and morphological traits associated with eriophyid mite infestation - Arunachalam`, V.; Jerard, B. Augustine; Apshara, S. Elain; Jayabose, C.; Subaharan, K.; Ravikumar, N.; Palaniswami, C. (Journal of Plantation Crops, 2013)
Observations were recorded on traits associated with mite infestation related at two stages of button on six different coconut cultivars over three years. Highly significant correlation was found between mite damage score with color or weight of tepal. Step-wise multiple regression of the data analysis showed color of inner tepal as major trait associated with infestation by eriophyid mite. Other traits are ratio of tepal weight to tepal area, per cent of buttons with pink discoloration or with resin, tepals of regular aestivation and gap between fruit and tepal. Digital phenotype data of 83 image files were used to calculate color signature and correlated the same to mite damage score over three years. Red spectral values were found to vary from 14 to 251, green values to 12 to 237 and blue to vary from 5 to 183. Spectral values red max, green max, 3* Red + Green max had high significant negative correlation (>-0.4) with mite damage. Color and firmness of fruits and tepals of three coconut varieties were further analyzed where, fruits and tepals of COD variety showed high red/green (a* value of Hunterlab) >12. Firmness of 3 month old tepal and fruit of Benualim (BGRT) tall variety was (penetrometer reading >38) higher than other varieties.